Rapidly Worsening Infective Endocarditis With Severe Mitral Stenosis - Yoshiyama, Daiki, MD; Morokuma, Hiroyuki, MD; Nagashima, Kiyotaka, MD; Baba, Kouhei, MD; Shichijo, Masahide, MD; Hayashi, Nagi, MD; Jinnouchi, Kouki, MD; Itoh, Manabu, MD, PhD; Yunoki, Junji, MD, PhD; Kamohara, Keiji, MD, PhD (JACC. Case reports, 2024)
AbstractInfective endocarditis (IE) rarely results in mitral stenosis (MS), but MS in patients with IE can be life-threatening. We present a case of prosthetic MS secondary to IE. A 69-year-old Japanese man underwent mitral valve replacement with a bioprosthetic valve 2 years previously. The patient presented with a 1-month history of illness, and we diagnosed prosthetic valve IE with severe MS and planned for time-sensitive surgery. However, the patient developed cardiogenic shock in response to prosthetic mitral valve obstruction while awaiting surgery. The patient then had to undergo emergency surgery. There are no management guidelines for IE-induced valve stenosis, whose treatment differs from that of valve regurgitation. Our literature review reveals that achieving survival in patients with MS secondary to IE is difficult without surgical intervention. Patients with MS caused by IE may require surgery, and specific criteria should be outlined in future guidelines.